Equine Asthma: Current Understanding and Future Directions - Couetil, Laurent; Cardwell, Jacqueline M.; Leguillette, Renaud; Mazan, Melissa; Richard, Eric; Bienzle, Dorothee; Bullone, Michela; Gerber, Vinzenz; Ivester, Kathleen; Lavoie, Jean-Pierre; Martin, James; Moran, Gabriel; et al. (Frontiers in Veterinary Science, 2020)
The 2019 Havemeyer Workshop brought together researchers and clinicians to discuss the latest information on Equine Asthma and provide future research directions. Current clinical and molecular asthma phenotypes and endotypes in humans were discussed and compared to asthma phenotypes in horses. The role of infectious and non-infectious causes of equine asthma, genetic factors and proposed disease pathophysiology were reviewed. Diagnostic limitations were evident by the limited number of tests and biomarkers available to field practitioners. The participants emphasized the need for more accessible, standardized diagnostics that would help identify specific phenotypes and endotypes in order to create more targeted treatments or management strategies. One important outcome of the workshop was the creation of the Equine Asthma Group that will facilitate communication between veterinary practice and research communities through published and easily accessible guidelines and foster research collaboration.